Coordinated Multi-Point MIMO Processing for 4G - Reis, C. (2014)
The concept of cooperative Multiple-Input-Multiple-Output (MIMO), also referred to as network MIMO, or as Coordinated Multi-Point Transmission (CoMP), was standardized in 3GPP Release 11. The goal of CoMP is to improve the coverage of high data rates and cell-edge throughput, and also to increase system throughput. In this paper we analyze only the latter scenario, using system level simulations in accordance with 3GPP guidelines. It is shown that the use of joint coordinated multipoint transmission achieves additional throughput gains. However, the gains depend on the scheduling type. This paper also indicates that the criterion of fairness is an important parameter when the number of users is high.